Identification of Potentially Therapeutic Immunogenic Peptides From Paracoccidioides lutzii Species - Silva, Leandro B. R.; Taira, Cleison L.; Cleare, Levi G.; Martins, Michele; Junqueira, Magno; Nosanchuk, Joshua D.; Taborda, Carlos P. (Frontiers in Immunology, 2021)
Paracoccidioidomycosis (PCM) is a endemic mycosis in Latin America caused by the thermodimorphic fungi of the genus Paracoccidioides spp. Paracoccidioides lutzii (PL) is one of the 5 species that constitute the Paracoccidioides genus. PL expresses low amounts of glycoprotein (Gp) 43 (PLGp43) and PLGp43 displays few epitopes in common with the P. brasiliensis (PB) immunodominant antigen PBGp43, which is commonly used for serological diagnosis of PCM. This difference in structure between the glycoproteins markedly reduces the efficiency of serological diagnosis in patients infected with PL. We previously demonstrated that peptide 10 (P10) from the PBGp43 induces protective immune responses in in vitro and in vivo models of PB PCM. Since, P10 has proven to be a promising therapeutic to combat PB, we sought to identify peptides in PL that could similarly be applied for treatment of PCM. PL yeast cell proteins were isolated from PL: dendritic cell co-cultures were subjected to immunoproteomics, and we identified 18 PL peptides that demonstrated in silic predictions for immunogenicity. We selected and synthetized 8 peptides that were applied to lymphocytes obtained from peptide-immunized or PL infected mice as well as to in vitro cultures with peptides or dendritic cells pulsed the peptides. The peptides LBR5, LBR6 and LBR8 efficiently promoted CD4+ and CD8+ T cells proliferation and dendritic cells pulsed with LBR1, LBR3, LBR7 or LBR8 stimulated CD4+ T cell proliferation. We observed increases of IFN-γ in the supernatants from primed T cells for the conditions with peptides without or with dendritic cells, although IL-2 levels only increased in response to LBR8. These novel immunoproteomes of Paracoccidioides lutzii will be employed to develop new peptide vaccine approaches and can help to develop a diagnostic assay with the proteins characterized. These findings clarified new peptides with a promising therapeutic profile to be use on this important neglected systemic mycosis.